Targeting B7-H3 Immune Checkpoint With Chimeric Antigen Receptor-Engineered Natural Killer Cells Exhibits Potent Cytotoxicity Against Non-Small Cell Lung Cancer - Yang, Shuo; Cao, Bihui; Zhou, Guangyu; Zhu, Lipeng; Wang, Lu; Zhang, Li; Kwok, Hang Fai; Zhang, Zhenfeng; Zhao, Qi (Frontiers in Pharmacology, 2020)
Chimeric antigen receptor (CAR)-modified natural killer (NK) cell therapy represents a kind of promising anti-cancer treatment because CAR renders NK cells activation and recognition specificity toward tumor cells. An immune checkpoint molecule, B7-H3, plays an inhibitory role in modulation of NK cells. To enhance NK cell functions, we generated NK-92MI cells carrying anti-B7-H3 CAR by lentiviral transduction. The expression of anti-B7-H3 CAR significantly enhanced the cytotoxicity of NK-92MI cells against B7-H3-positive tumor cells. In accordance with enhanced cytotoxicity, the secretions of perforin/granzyme B and expression of CD107a were highly elevated in anti-B7-H3 CAR-NK-92MI cells. Moreover, compared to unmodified NK-92MI cells, anti-B7-H3 CAR-NK-92MI cells effectively limited tumor growth in mouse xenografts of non-small cell lung cancer and significantly prolonged the survival days of mice. This study provides the rationale and feasibility of B7-H3-specific CAR-NK cells for application in adoptive cancer immunotherapy.